2023
DOI: 10.1021/acs.energyfuels.3c02773
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nanostructured Transition Metal Phosphide-Driven Electrocatalytic Oxygen Evolution Reaction

Tarik Aziz,
Mahejabeen A. Haque,
Sukanta Saha
et al.

Abstract: The H2-mediated energy transduction strategy emerged as one of the best options in our journey toward a carbon-neutral energy infrastructure where the water-splitting reaction remains a key component. Oxygen evolution reaction (OER) is one of the principal segments of water electrolysis as well as hydrogen production. However, the OER is a slow reaction in nature and demands the intervention of a catalyst to drive it at a commendable rate and efficiency, ensuring its practical application. In recent years, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…https://doi.org/10.26434/chemrxiv-2024-0fj98 ORCID: https://orcid.org/0000-0001-8533-7347 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 2 One of the important rapidly developing research avenues for this class of materials is their application in various catalytic processes including photocatalysis, 29,30 organic catalysis, [31][32][33][34] electrocatalysis for CO2-conversion, [35][36][37][38][39] hydrogen and oxygen evolution [40][41][42][43][44][45][46] . Over the years, their catalytic performance characteristics have been steadily approaching those of state-of-the-art systems based on noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.26434/chemrxiv-2024-0fj98 ORCID: https://orcid.org/0000-0001-8533-7347 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 2 One of the important rapidly developing research avenues for this class of materials is their application in various catalytic processes including photocatalysis, 29,30 organic catalysis, [31][32][33][34] electrocatalysis for CO2-conversion, [35][36][37][38][39] hydrogen and oxygen evolution [40][41][42][43][44][45][46] . Over the years, their catalytic performance characteristics have been steadily approaching those of state-of-the-art systems based on noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Studies have shown that under the anodic potential of the OER, the surface of NiFe-based transition metal phosphides would transform into oxides and (oxy)hydroxides. 24 Feng et al showed that Ni 2 P exhibits good OER activity, with a current density of 10 mA cm −2 at an overpotential of 290 mV, which is much better than those of nickel hydroxide and oxide. Besides, the addition of another metal to form ternary metal phosphides can further improve the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%